E-081 Combined transradial and transvenous accesses in the treatment of carotid cavernous fistulae. (23rd July 2022) - Babici, D; Johansen, P; Snelling, B
Abstract : Introduction: The expansion of indications for neurointerventional procedures, combined with the need to treat a diverse patient population, has driven a need for broader access options. Concurrent arterial and venous access is often necessary for diagnosis and treatment of various neurovascular diseases. Although complication rates are low, life-threatening severe complications have been reported with these access methods. Moreover, venous access through traditional routes can be challenging in patients with large body habitus. There is a growing trend of utilizing radial artery access for neuroendovascular procedures due to the increased ease of access and similar efficacy. Nevertheless, the use of upper limb veins in neurointerventional procedures is still rare. Upper extremity transvenous access (UETV) has recently emerged as an alternative strategy for the neurointerventionalists, but data is limited. Methods: C ase study Case Description: Case #1 An 82-year-old male underwent successful mechanical thrombectomy for large vessel occlusion of the right middle cerebral artery (MCA) M1 segment. During the procedure, he sustained perforation of the cavernous internal carotid artery (ICA) at the posterior genu due to severe tortuosity and underlying atherosclerosis, resulting in a direct CCF. The next day, the patient was noted to have worsened visual acuity of the right eye along with chemosis and proptosis. The senior author was consulted, and the decision was made to perform embolization of the CCF using combined TRA and UETV, with hopes of preventing further loss of vision and restoring baseline visual acuity. Transvenous coil embolization to obliterate the CCF went without complications, and the patient's vision was noted to have returned to his pre-operative baseline the following day. No access site complications were encountered. Case #2 A 71-year-old male presented to clinic with a three-week history of decreased visual acuity in the left eye. Physical examination was significant for left sided vision loss, lid lag, and chemosis without proptosis. Cerebral angiography revealed a CCF supplied by both indirect internal and external carotid feeding arteries with drainage into the superior ophthalmic vein and ipsilateral inferior petrosal sinus. The patient underwent transvenous coil embolization of his left carotid cavernous fistula using combined TRA and UETV. The procedure went without complications. The patient was discharged on post-operative day one with improvement in his visual acuity. Conclusion: No access site or procedural complications were noted in either of the authors' cases. Obtaining venous access with an IV in the pre-operative area likely decreased the time required to obtain venous access compared to standard TVA. Both patients were able to benefit from early mobility and ambulation compared to standard transfemoral approaches. Combined TRA and UETV is a feasible, promising access strategy for patients and may confer the same safety and patient satisfaction outcomes that have been seen with TRA in neurointerventional procedure. Further studies are needed to elucidate the exact impact this strategy has on patient outcomes and satisfaction.> Disclosures: D. Babici: None. P. Johansen: None. B. Snelling: None.